“Socioeconomical Factors Inf luencing Tributation Formality in Restaurants from Santa Anita y Miraflores Districts at Lima-Perú” - Uribe Hernández, Yrene (2014)
To determine the main socioeconomical factors that influence on the fiscal duties observance in Restaurants from Santa Anita and Miraflores districts, this study was performed. 150 restaurants per district were studied. A validated survey by Cornbach´s alpha was applied. Frequencies were calculated and the socioeconomical factors influence was determined using Xi2 test.  Santa Anita showed higher dispersion than Miraflores and male gender was prevalent. There  were differences in education, tributary training, the kind of business, importance of team work, the most affecting tax, citizenship security and vial access importance, supervisionand control and tributary encouragement by SUNAT, influence of bank credit, or mortgage and generated incomes over lifestyle; and the fiscal duties observance. They agree about considering fiscal responsibilities as the main problem and the monthly average income. Finally, all the factors significatively influenced on the observance of task duties